What drives the location choice of new manufacturing plants in Germany? - Astrid Krenz (ZBW - Leibniz Information Centre for Economics, 2020)
Almost 30 years after German reunification, a persistent gap in different firm performance measures exists between East and West Germany. In this paper I focus on the differences in new German manufacturing plants' location choices across the German district-free cities and districts and investigate its regional determinants. For that purpose, I construct a novel, rich regional- and plant-level dataset based on the Official Firm Statistics from the German Federal Statistical Office and the Offices of the Laender. The analysis provides first-time evidence regarding how in particular the location decision of plants in the German economy is in uenced by regional road infrastructure as well as regional structural funding. The effects are economically important and significant. The results reveal that a 10 percent increase in plant agglomeration increases the odds of a new plant to locate in the region by 12 percent. A 10 percent decrease of travel time on roads increases the odds of a plant to locate by 4 percent in Germany overall, by 7.6 percent among East German regions and by 26.5 percent in particular for large plants in the East German regions. A 10 percent larger population increases the odds to locate by 8.7 percent. A 10 percent increase in regional structural funding for infrastructure purposes increases the odds to locate in a region in East Germany by 8.3 percent in particular for large plants. Policy implications emerge that address in particular the improvement of infrastructure and support to reap the benefits that arise from agglomeration externalities.
Keywords: D22; L25; R11; R12; 330; Firm location choice; regional road infrastructure; Germany; agglomeration economies; regional structural funding; East-West gap; conditional logit; nested logit.